2018
DOI: 10.3168/jds.2018-15162
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of dietary addition of N-carbamoylglutamate on milk composition in mid-lactating dairy cows

Abstract: The present study was conducted to investigate the effect of N-carbamoylglutamate (NCG) on milk production and composition in mid-lactating Holstein dairy cows. Sixty multiparous cows with a mean body weight of 669 kg (standard deviation = 71) and 176 days in milk (standard deviation = 55) were blocked based on parity and milk production and randomly assigned into 4 treatments, a basal diet supplemented with 0, 10, 20, or 40 g of NCG/d per cow. Milk yield and composition were recorded weekly, whereas dry matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
5
17
2
Order By: Relevance
“…The greater DMI in cows consuming NCG in our study could be related to the higher levels of NO in plasma. However, no difference in DMI was observed with the addition of NCG in our previous studies ( Chacher et al., 2014 ; Gu et al., 2018 ). After comprehensively analyzing 35 studies on feeding with the same Met product, Patton (2010) found that the DMI response of cows varied based on the differences in experimental lengths and lactation stages.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The greater DMI in cows consuming NCG in our study could be related to the higher levels of NO in plasma. However, no difference in DMI was observed with the addition of NCG in our previous studies ( Chacher et al., 2014 ; Gu et al., 2018 ). After comprehensively analyzing 35 studies on feeding with the same Met product, Patton (2010) found that the DMI response of cows varied based on the differences in experimental lengths and lactation stages.…”
Section: Discussioncontrasting
confidence: 57%
“…The samples were centrifuged at 3,000 × g for 15 min to collect plasma which was then frozen at −20 °C until subsequent analysis. Plasma biochemical variables were analyzed using an AutoAnalyzer 7020 instrument (Hitachi High-technologies Corporation, Tokyo, Japan) with colorimetric commercial kits (Ningbo Medical System Biotechnology Co., Ltd.) to determine urea nitrogen, total protein, albumin, non-esterified fatty acids (NEFA), β-hydroxybutyrate (BHB), triglyceride, glucose, total bilirubin, cholesterol, globulin, glutamic oxaloacetic transaminase (AST), and glutamic-pyruvic transaminase (ALT) ( Gu et al., 2018 ). Plasma concentration of NO was measured using the nitrate reductase method with a NO assay kit (Nanjing Jiancheng Bioengineering Research Institute, Nanjing, China, No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amounts of feed offered and refused were recorded according to Gu et al (2018) [17] to determine dry matter intake (DMI). The TMR samples were collected weekly for dry matter (DM, 105 °C for 5 h), crude ash, ether extract (EE), crude protein (CP), and acid detergent fiber (ADF), according to AOAC procedures (method 942.05, 920.39, 988.05, and 973.18, respectively), and neutral detergent fiber (NDF) with sodium sulfite and amylase was analyzed [18].…”
Section: Methodsmentioning
confidence: 99%
“…Arginine participates in protein synthesis and metabolism to improve intestinal absorption function, hormones secretion and nitric oxide (NO) production, which ultimately bene ts the growth, development and production performance of dairy cows [1,2]. However, with the high arginase activity or rumen degradation, arginine is rapidly degraded with short biological half-time.…”
Section: Introductionmentioning
confidence: 99%